2021
DOI: 10.15581/003.34.1.93-108
|View full text |Cite
|
Sign up to set email alerts
|

Will better performing health-care services have higher profiles and be more active on social media? A comparative study between hospitals from Colombia and Spain

Abstract: Hospitals make increasingly more use of social media. The basic hypothesis of this study is that the more developed the health care services of a country are, the higher the communicative activity of its hospitals will be on social media. Moreover, the highest presence and activity on social media will be associated with the most prestigious hospitals in countries with fewer economic resources. The presence of the most prestigious hospitals in both Colombia and Spain on Facebook, Twitter, YouTube and Instagram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The literature has focused on the communication strategies of various institutions (e.g, Busto-Salinas, 2021;Ferrer-Serrano et al, 2020;Losa-Díaz et al, 2020;Martínez-Cardama & Pacios, 2020;Tuñón-Navarro & Carral-Vilar, 2021) but it is still necessary to deepen the way in which communication has been managed by companies in order to increase their legitimacy and their capacity to establish dialogue and interaction with stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature has focused on the communication strategies of various institutions (e.g, Busto-Salinas, 2021;Ferrer-Serrano et al, 2020;Losa-Díaz et al, 2020;Martínez-Cardama & Pacios, 2020;Tuñón-Navarro & Carral-Vilar, 2021) but it is still necessary to deepen the way in which communication has been managed by companies in order to increase their legitimacy and their capacity to establish dialogue and interaction with stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has analyzed the communicational styles and perceived emotions of the messages posted by governmental authorities (Losa-Díaz et al, 2020). In this context, recent research has also shown that politicians have not favored dialogue in social networks with groups of interest such as civil society (Tuñón-Navarro & Carral-Vilar, 2021) and that healthcare institutions, such as hospitals, did not have a very active presence in social networks (Busto-Salinas, 2021). Other studies have analyzed the role of universities, proving their growth in Twitter activity and increased interaction with their users (Ferrer-Serrano et al, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation